X-Ray Classification of Pneumonia by Neural Networks Convolution using Vgg Architecture - Toni Arifin; Naufal Hidayah Surya (Sistemasi: Jurnal Sistem Informasi, 2022)
Pneumonia is one of the deadliest diseases, killing 2-3 million people in developed countries like the United States. Based on WHO's view, pneumonia is one of the leading causes of death in children worldwide, WHO says many children under the age of 5 have died from the disease. And in 2017, the World Health Organization (commonly known as WHO) reported that  pneumonia had claimed the lives of 800,000 children under the age of 5. This is  why  researchers developed this program,  to help the  public  diagnose pneumonia. In this study, we generated a Deep Learning model using the CNN (Convolutional neural network) approach using the VGG16 architecture for thoracic pneumonia classification and normalization. The results of this study show that the Convolution neural network method can classify chest X-ray results  with pneumonia with the highest accuracy of 0.9772